2019
DOI: 10.1186/s13584-019-0321-9
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation of hysterectomy rates in the Israeli health care system during the years 2007–2016

Abstract: Background In 2014 the OECD published a report regarding inter-regional variation of hysterectomies in 13 countries including Israel. Variance in hospital admission rates were also reported. The Israeli Ministry of Health has set as one of its main goals the reduction in differences in health care, particularly between the country’s periphery and central regions. These variations may reflect differences in characteristics, resource allocation, and medical staff employment, expertise and training. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 10 publications
1
12
1
Order By: Relevance
“…While most studies investigating differences in use of hysterectomy have been longitudinal, studies on temporal variations within one country are rare. Additionally, many of the studies examining regional variation do so with total hysterectomy rates [ 5 , 7 , 11 , 12 ] and only a few separate between rates for benign and malign conditions [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…While most studies investigating differences in use of hysterectomy have been longitudinal, studies on temporal variations within one country are rare. Additionally, many of the studies examining regional variation do so with total hysterectomy rates [ 5 , 7 , 11 , 12 ] and only a few separate between rates for benign and malign conditions [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Israel's Ministry of Health, including sub-units such as the Gertner Institute for Epidemiology and Health Policy Research and the Israel Center for Disease Control, was the database owner for 10 of these articles. Maccabi Healthcare Services 5 and the Hadassah Medical Organization were each the database owners for 2 of the articles, and the Ministry of Defense, Sha'are Zedek Medical Center, and Terem 6 were each the database owners for one of the articles. In 16 of these articles, there was at least one author from within the organization that owns the relevant database.…”
Section: Further Information On the 2019 Articles That Relied On Datamentioning
confidence: 99%
“…In short, investigators from outside the owning organization are occasionally Interestingly, of the 11 integrative articles the IJHPR published in 2019, 2 explored the impact of national program or policy changes and 1 explored the impact of a health plan program change. 5 Maccabi is Israel's second largest health plan, with over 2 million members 6 Terem is a network of emergency medical centers involved in articles based on databases, but almost always in conjunction with investigators from within the owning organization and rarely as the lead authors.…”
Section: Further Information On the 2019 Articles That Relied On Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1970s, numerous studies have shown variation in hysterectomy practices between countries or regions within countries (7,12,13). Those regional variations are potentially a sign of the nonoptimal use of resources or healthcare inequalities (8,14). It is, therefore, important to identify the causes of the unexplained overuse of hysterectomies in some regions.…”
Section: Introductionmentioning
confidence: 99%